How are journal impact, prestige and article influence related? an application to neuroscience - Chang, C.; Mcaleer, M.; Oxley, Leslie (2011)
The paper analyzes the leading journals in neurosciences using quantifiable research assessment measures (RAM), highlights the similarities and differences in alternative RAM, shows that several RAM capture similar performance characteristics of highly cited journals, and shows that some other RAM have low correlations with each other, and hence add significant informational value. Alternative RAM are discussed for the Thomson Reuters ISIWeb of Science database (hereafter ISI). The RAM that are calculated annually or updated daily include the classic 2-year impact factor (2YIF), 5-year impact factor, immediacy (or zeroyear impact factor), Eigenfactor score, article influence score, C3PO (citation performance per paper online), h-index, Zinfluence, PI-BETA (papers ignored by even the authors), 2-year and historical selfcitation threshold approval ratings, impact factor inflation, and cited article influence (CAI). The RAM are analyzed for 26 highly cited journals in the ISI category of neurosciences. The paper finds that the Eigenfactor score and PI-BETA are not highly correlated with the other RAM scores, so that they convey additional information regarding journal rankings, that article influence is highly correlated with some existing RAM, so that it has little informative incremental value, and that CAI has additional informational value to that of article influence. Harmonic mean rankings of the 13 RAM criteria for the 26 highly cited journals are also presented. Emphasizing the 2YIF of a journal to the exclusion of other informative RAM criteria is shown to lead to a distorted evaluation of journal performance and influence, especially given the informative value of several other RAM. © 2011 Taylor & Francis.